Model Predictive Current Control Strategy for Improved Dynamic Response in Cascaded H-Bridge Multilevel Inverters - Baek, Ju Yoen; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2024)
This paper proposes a model predictive current control technique for fast dynamic response in cascaded H-bridge multilevel inverters. Typically, cascaded H-bridge multilevel inverters are controlled using the PI controller with a pulse-width modulation or the model predictive control method through system modeling. However, PI controller has a limitation in terms of dynamic responses. In contrast, the model predictive control method does not require tuning of proportional and integral gain values and does not use pulse-width modulation. Thus, the model predictive control has a fast response and a flexible control technique. Applying the conventional model predictive control to multilevel inverters results in a large amount of computation because of a large number of voltage vectors. The proposed method suggests a model predictive control strategy to determine output voltage vectors and switching states based on the position of a reference voltage. Furthermore, the proposed method reduces the computation compared to conventional model predictive control techniques, which calculate all voltage vectors, and achieves faster responses than conventional method that uses adjacent vectors. The effectiveness of the proposed model predictive current control method was validated through simulation and experimental results.
Keywords: Cascaded H-bridge; Fast dynamic response; Model predictive; Model predictive current control; Model-predictive control; Multi Level Inverter (MLI); Multilevels; PI Controller; Predictive current control; Voltage vectors; Cascaded H-bridge; Fast dynamic response; Model predictive current control; Multilevel inverter